Impact of pricing mechanism on IPO oversubscription: evidence from Pakistan stock exchange. Issue 2 (5th March 2020) - Mehmood, Waqas; Mohd-Rashid, Rasidah; Ahmad, Abd Halim
Abstract : Purpose: The purpose of this paper is to examine the effects of pricing mechanism on initial public offerings (IPOs) oversubscription in Pakistan. Design/methodology/approach: This study used cross-sectional data to analyse 85 listed IPOs on the Pakistan stock exchange during the period of 2000-2017 to assess hypotheses related to influential determinants of IPO oversubscription. Accordingly, ordinary least square, robust regression and quantile regression approaches were applied in this study to evaluate the factors that influenced oversubscription. Findings: The outcome displayed pricing mechanism is negatively significant with an oversubscription of IPOs. This indicates firms using the fixed-price mechanism signalled higher information asymmetry and uncertainty in their value. Thus, investors are aware that they will be offset with underpricing, and it is expected the demand will be higher for the particular IPOs. Research limitations/implications: This study is entirely focused on the available information of prospectus that should not be ignored by potential investors at the time of subscription of IPO. Therefore, the study contributes to extending the available literature in signalling theory whereby issuers should consider using the book-building pricing mechanism in enhancing the efficiency of the IPO offer price during the listing. Originality/value: This paper provides evidence for the determinants of the IPO oversubscription.